The National Plan of Integrated Logistics and the insertion process of the state of Mato Grosso do Sul in the “Investment Program in Logistics: roads and railways” - Mauro da Silva Fernandes, Roberto; Oliveira Souza, Adáuto (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article aims to hold a discussion regarding the institutionalization of the unity of opposites, through the National Plan of Integrated Logistics (PNLI), especially as part of a national development strategy (new developmentalism) and reflect on the insertion of state of Mato Grosso do Sul in the "Investment Program in Logistics: roads and railways." We believe that the unity of opposites is present in said government plan, because it seeks to unite the opposing tendencies of running the government and the private sector, the state and the market. To achieve the proposed objectives bibliographic and documentary research, which focus on economic policy, institutions, transport geography and economic geography was performed.